Prevalence of Antenatal Depressive Symptoms and its Associated Factors among Pregnant Nepalese Women with and Without Low Back- and/or Pelvic Girdle Pain - Stuge, Britt; Sørensen, Hjørdis; Acharya, Ranjeeta Shijagurumayum; Tveter, Anne Therese (Journal of Nepal Health Research Council, 2022)
Background: Pregnant women with health problems have shown higher odds of depressive symptoms. Evidence suggests a co-morbid relation between pregnancy-related low back pain and/or pelvic girdle pain and the risk of depression. The aims were to investigate the prevalence of symptoms of depression among pregnant Nepalese women in general and among pregnant Nepalese women with low back pain and/or pelvic girdle pain and to identify factors associated to symptoms of depression. Methods: A cross-sectional study using standardized condition-specific questionnaires with response from 1284 pregnant Nepalese women. Multivariate logistic regression analysis determined variables associated with symptoms of depression.Results: Twenty-one percent of the women presented with moderate to high symptom level of depression, compared to 29% of the women with low back pain and/or pelvic girdle pain. Low education, living without husband, no rest during work, higher self-reported disability, higher pain intensity and symptoms of pelvic organ prolapse were associated with higher odds of symptoms of depression among the women with low back pain and/or pelvic girdle pain. For the total sample, fetching water and having symptoms of low back pain and/or pelvic girdle pain and living without husband were associated to symptoms of depression.Conclusions: Twenty-one percent of the pregnant women reported moderate to high symptom level of depression. The proportion of women with symptoms of depression was significantly higher among the women categorized as having low back pain and/or pelvic girdle pain. Our findings highlight the need to address both emotional and physical needs among pregnant Nepalese women.Keywords: Depression; low back pain; maternal health; Nepal; pelvic girdle pain.